2015
DOI: 10.3389/fpsyg.2015.00847
|View full text |Cite
|
Sign up to set email alerts
|

Non-verbal sensorimotor timing deficits in children and adolescents who stutter

Abstract: There is growing evidence that motor and speech disorders co-occur during development. In the present study, we investigated whether stuttering, a developmental speech disorder, is associated with a predictive timing deficit in childhood and adolescence. By testing sensorimotor synchronization abilities, we aimed to assess whether predictive timing is dysfunctional in young participants who stutter (8–16 years). Twenty German children and adolescents who stutter and 43 non-stuttering participants matched for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 99 publications
9
115
1
3
Order By: Relevance
“…Recent studies revealed that some of the tasks included in BAASTA, in particular paced tapping, are sensitive to peculiar disorders of beat-based timing in different populations. For example, synchronization consistency is particularly low in adult beat-deaf participants (Sowiński & Dalla Bella, 2013), in children suffering from developmental stuttering (Falk et al, 2015) and in preschoolers who score poorly in early language tests (e.g., phonological awareness and naming tasks; Woodruff Carr, Tierney, White-Schwoch, & Kraus, 2016;Woodruff Carr et al, 2014). Synchronization accuracy (i.e., whether participants anticipate or not the beat) is also impaired in children with developmental stuttering, who tend to anticipate the beat more than controls do.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies revealed that some of the tasks included in BAASTA, in particular paced tapping, are sensitive to peculiar disorders of beat-based timing in different populations. For example, synchronization consistency is particularly low in adult beat-deaf participants (Sowiński & Dalla Bella, 2013), in children suffering from developmental stuttering (Falk et al, 2015) and in preschoolers who score poorly in early language tests (e.g., phonological awareness and naming tasks; Woodruff Carr, Tierney, White-Schwoch, & Kraus, 2016;Woodruff Carr et al, 2014). Synchronization accuracy (i.e., whether participants anticipate or not the beat) is also impaired in children with developmental stuttering, who tend to anticipate the beat more than controls do.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, based on the data obtained in a relatively small sample of non-musicians, the battery can sensitively identify individual differences in perceptual and sensorimotor timing skills. Hence, BAASTA can serve to uncover individuals with spared or impaired rhythmic skills in healthy participants without musical training and in clinical populations (e.g., Benoit et al, 2014;Falk, Müller & Dalla Bella, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations